Differential Effects of 2-Deoxyglucose and Glucose Deprivation on 4-Hydroxynonenal Dependent Mitochondrial Dysfunction in Primary Neurons - Dodson, Matthew; Benavides, Gloria A.; Darley-Usmar, Victor; Zhang, Jianhua (Frontiers in Aging, 2022)
Mitochondrial dysfunction and metabolic decline are prevalent features of aging and age-related disorders, including neurodegeneration. Neurodegenerative diseases are associated with a progressive loss of metabolic homeostasis. This pathogenic decline in metabolism is the result of several factors, including decreased mitochondrial function, increased oxidative stress, inhibited autophagic flux, and altered metabolic substrate availability. One critical metabolite for maintaining neuronal function is glucose, which is utilized by the brain more than any other organ to meet its substantial metabolic demand. Enzymatic conversion of glucose into its downstream metabolites is critical for maintaining neuronal cell growth and overall metabolic homeostasis. Perturbation of glycolysis could significantly hinder neuronal metabolism by affecting key metabolic pathways. Here, we demonstrate that the glucose analogue 2-deoxyglucose (2DG) decreases cell viability, as well as both basal and maximal mitochondrial oxygen consumption in response to the neurotoxic lipid 4-hydroxynonenal (HNE), whereas glucose deprivation has a minimal effect. Furthermore, using a cell permeabilization assay we found that 2DG has a more pronounced effect on HNE-dependent inhibition of mitochondrial complex I and II than glucose deprivation. Importantly, these findings indicate that altered glucose utilization plays a critical role in dictating neuronal survival by regulating the mitochondrial response to electrophilic stress.